2014
DOI: 10.1098/rsif.2014.0852
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of collagen gel contraction by porcine aortic valvular interstitial cells

Abstract: Despite a high incidence of calcific aortic valve disease in metabolic syndrome, there is little information about the fundamental metabolism of heart valves. Cell metabolism is a first responder to chemical and mechanical stimuli, but it is unknown how such signals employed in valve tissue engineering impact valvular interstitial cell (VIC) biology and valvular disease pathogenesis. In this study porcine aortic VICs were seeded into three-dimensional collagen gels and analysed for gel contraction, lactate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In the context of VICs, we have previously shown that ORR correlated with cellular proliferative potential when VICs were cultured under different media conditions 24 . We have also previously reported that an increase in pathological stretch reduced the ORR in VICs, suggesting that the involved signaling pathways and VIC pathological function are closely linked to the overall cellular metabolic state 14,19,24 . However, TPEF imaging metrics -ORR and mitochondrial clustering have not yet been shown to predict or correlate with the pathological changes in VICs during early CAVD progression.…”
mentioning
confidence: 54%
“…In the context of VICs, we have previously shown that ORR correlated with cellular proliferative potential when VICs were cultured under different media conditions 24 . We have also previously reported that an increase in pathological stretch reduced the ORR in VICs, suggesting that the involved signaling pathways and VIC pathological function are closely linked to the overall cellular metabolic state 14,19,24 . However, TPEF imaging metrics -ORR and mitochondrial clustering have not yet been shown to predict or correlate with the pathological changes in VICs during early CAVD progression.…”
mentioning
confidence: 54%
“…Collagen gels for contraction assays were prepared by using of Rat tail collagen I (Serva, Germany), 10× DMEM, 1 M NaOH (final pH 7.4) and mixed with cells (1 × 10 6 /ml) in 8:1:1:1 ratio previously described in Kamel et al (), with final concentration 2 mg/ml. Gel–cells suspension (triplicates) was pipetted into 96 wells pre‐coated with BSA and allowed polymerized in 5% CO 2 at 37°C for at least 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the metabolism of circulating tumor cells is different than that of primary tumor cells, with a predilection for increased oxidative phosphorylation in circulating tumor cells (Lebleu et al, 2014). Cellular metabolism is a key first responder to changes in the chemical and mechanical environment (Kamel et al, 2014). Despite this small but growing data, the direct effect of collagen density on cellular metabolism has not been well established.…”
Section: Introductionmentioning
confidence: 99%